Skuteczność reklamy w przedsiębiorstwie przemysłu tłuszczowego - Nieżurawski, Lech; Orłowska, Aldona (The Efficiency of Advertising in Fat Industry Company, 2005)
The article analyzes basic decisions related to the management of advertising in fat industry company. These activities contain the definition of target market and also the efficiency of advertising aim towards the support of positive image of brand, underlining the unique features and high quality. To realize an effective advertising campaign in the surveyed company it is necessery to obtain information concerning the advertising expenses on the fat markets, and first of all the segments expenses: oil and olive oil. This information is very important in making the advertising campaign more efficient than competition does.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 125-131